2015
DOI: 10.1007/s11270-015-2612-2
|View full text |Cite
|
Sign up to set email alerts
|

Decolourization of Congo Red by Ganoderma lucidum Laccase: Evaluation of Degradation Products and Toxicity

Abstract: Several laccases from different sources have been used in dye decolourization processes. However, only in a reduced number of studies have efforts been done to identify the metabolites produced by the enzymatic treatment as well as to evaluate the toxicity of degradation products. Taking these gaps into account, the objective of this work was to use a laccase from Ganoderma lucidum in the decolourization of the synthetic dye Congo red (C.I. No. 22120, Direct Red 28), largely used in the textile industry. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 38 publications
2
10
0
5
Order By: Relevance
“…Regarding the manganese peroxidase, its production was negligible under all experimental conditions assayed. Similar results have been reported by Mota et al (2015) who observed that G. lucidum did not produce MnP.…”
Section: Resultssupporting
confidence: 91%
“…Regarding the manganese peroxidase, its production was negligible under all experimental conditions assayed. Similar results have been reported by Mota et al (2015) who observed that G. lucidum did not produce MnP.…”
Section: Resultssupporting
confidence: 91%
“…The FTIR spectra of PSP, DPSP and CR in Figure exhibit the following absorption bands and they are assigned referring to the literatures . In the spectrum of PSP, the bands located at 711.87, 876.31, and 1420.02 cm −1 are ascribed to the in‐plane bending, out‐of‐plane bending, and asymmetric stretch vibrations of CO32 groups, respectively .…”
Section: Resultsmentioning
confidence: 89%
“…The selected dyes are common pollutants in the environment, but nevertheless they are less studied compared to other dyes such as Methylene Blue (Chairunnisa et al 2016;Saghanejhad Tehrani and Zare-Dorabei 2016) and Red Congo dyes (Dawood and Sen 2012;Mota et al 2015). The physicochemical properties and the composition of the prepared bioadsorbents were studied with the help of characterization methods.…”
Section: Introductionmentioning
confidence: 99%